The catholic church as a structuring agent for the city of Salvador in the colonial period - De Almeida Vasconcelos, Pedro (Geografares, 2020)
Salvador was the capital of the Portuguese America from 1549 until 1763. It was also the second city of the Portuguese Empire up to the 19th century. The Catholic Church together with the State was the main agents that structured the city of Salvador during the whole colonial period. The Secular Church related to the State through the Padroado was responsible for the implementation and maintenance of the Cathedral, churches and parishes; the religious orders with their convents were important structural elements of the urban space while the laic orders owned churches and many urban properties and corresponded to the structuring of a slave society.
Keywords: Catholic Church; Agents; Salvador